A Service-Oriented Framework for the Development of Home Robots. (13th February 2013) - Yang, Tsung-Hsien; Lee, Wei-Po
In recent years, researchers have been building home robots able to interact and work with people. Yet, because of the complicated and independent robot development environments, it is not always easy to share and reuse robot code created by different providers. In this work, we present an ontology-based framework that integrates service-oriented computing environments with the standard web interface to develop reusable robotic services. In addition to the service discovery, selection, and composition processes often performed by traditional web services, our work also includes an adaptive mechanism through which the user can iteratively modify composite robotic services to suit his or her needs. The proposed methodology has been implemented and evaluated, and the results show that our framework can be used to build robotic services successfully.